Early Management of Patients With Acute Heart Failure: State of the Art and Future Directions—A Consensus Document from the SAEM/HFSA Acute Heart Failure Working Group. (25th November 2014) - Collins, Sean P.; Storrow, Alan B.; Levy, Phillip D.; Albert, Nancy; Butler, Javed; Ezekowitz, Justin A.; Michael Felker, G.; Fermann, Gregory J.; Fonarow, Gregg C.; Givertz, Michael M.; Hiestand, Brian; Hollander, Judd E.; et al.
Abstract Heart failure (HF) afflicts nearly 6 million Americans, resulting in 1 million emergency department (ED) visits and over 1 million annual hospital discharges. The majority of inpatient admissions originate in the ED; thus, it is crucial that emergency physicians and other providers involved in early management understand the latest developments in diagnostic testing, therapeutics, and alternatives to hospitalization. This article discusses contemporary ED management as well as the necessary next steps for ED‐based acute HF research.